Evaluation of Eu Cohesion Policy Impact on Regional Convergence: Do Culture Differences Matter? - Butkus Mindaugas; Matuzevičiūtė Kristina (Economics and Culture, 2016)
Attention to the harmonised economic growth by promoting regional economic convergence was paid in the 1960s, at the commencement of European economic integration. It served as a basis for initiation of programs intended to reduce disparities among regions. For the current programming period (2014-2020) over 350 billion euro was allocated to promote cohesion (more than 340 billion for 2007-2013 and about 213 billion for 2000-2006) and a considerable part of that funding went specially to promote regional convergence; therefore, the analysis of regional convergence in the EU countries is essential due to both economic and financial reasons. Regional policy can be considered successful if regional disparities are found to be decreasing; however, research on convergence/divergence issue has not provided any unambiguous conclusions. We aim to enrich this field of analysis by incorporating cultural dimension while analysing the factors influencing regional convergence. In order to identify a causal link between culture and economic outcomes, we define culture as the customary beliefs and values that ethnic, religious and social groups transmit almost unchanged from generation to generation. Our research hypothesis is that regional policy impact on regional convergence differs between groups of countries characterised by historically diverse cultural experience. Using panel data approach like FD and covering the two last programming periods along with a set of variables to control country-specific economic environment, we investigate whether the success of Cohesion policy has depended on cultural differences in the north, south, west and central-east groups of European countries.